Invasion genetics of alien insect pests in China: Research progress and future prospects - Dong CHU; Wan-mei QU; Lei GUO (Journal of Integrative Agriculture, 2019)
An unwelcome side effect of the globalization of the world's economy and dramatic increase in human mobility and trade has been a marked increase in species invasions that have posed severe threats to the ecological, economic, and/or social stability of the introduced regions. In this review, we analyzed the application of molecular markers in invasion genetics of invasive alien insect pests (IAIPs) in China based on a bibliometric survey. Our report discusses the considerable progress that has been made during the past two decades in understanding the invasion genetics of IAIPs in China. We reviewed the major findings in the main topics including the effects of origin and routes of invasion on genetic structure, spatial and temporal genetic changes, factors contributing to the genetic changes of IAIPs, and genetic mechanisms involved in IAIPs' invasions. On the other hand, some of these research areas remain relatively unexplored in China, especially those pertaining to spatial and temporal genetic changes of IAIPs and genetic mechanisms of IAIPs' invasions. Finally, the future research prospects of IAIPs in China are discussed. We hope this review will stimulate an interest in and provide an increased understanding of the field of invasion genetics of IAIPs in China, and provide a basis for future research in this area.